Pandangan Tokoh Falak tentang Elongasi pada Penentuan Awal Syawal 1443 H dalam Kriteria Neo MABIMS di Indonesia - Nur Aini; Youla Afifah Azkarrula (Astroislamica: Journal of Islamic Astronomy, 2024)
Indonesia implemented the Neo MABIMS criteria for the first time at the beginning of Ramadan and Shawwal 1443 H/2021 AD. However, the application of this new criterion raises an issue of problems in determining the beginning of Shawwal 1443 H. This problem arises in the implementation of the elongation parameter. So there is a confusion that arises for experts and observers of falak in the case of the beginning of the month. This will lead to uncertainty if it is not studied. Therefore, this research was raised using field research and  qualitative approach. Data collection in this study was carried out by interviewing Indonesian Falak figures and some data using documentation. The data obtained were analyzed using descriptive analysis method and triangulation method to obtain valid results. The results of this study indicate that the Neo MABIMS criteria are the result of a new agreement from the renewal of previous criteria with higher parameters. The problem in determining the beginning of Shawwal 1443 H by implementing the Neo MABIMS criteria arises due to the lack of agreement on the use of geocentric or topocentric elongation parameters. In this Shawwal case, the experts decided to use geocentric elongation by considering maslaha (public interest). However, for this case, it was still in an ambiguous state due to there were two paradigms from the Falak figures regarding the implement of elongation, namely geocentric and topocentric.